Geomorphological evolution of the Serra da Canastra occidental border: proposition of a relief taxonomy for studies on transitional areas - de Cortes, João Paulo Soares; Lupinacci, Cenira Maria [UNESP]; Morales, Norberto (Revista Brasileira de Geomorfologia, 2022)
The Serra da Canastra's occidental border is characterized as a transition zone between two distinctive morphostructural domains. To West, there is the prevalence of phanerozoic terrains of the Paraná Sedimentary Basin, constituted by sedimentary and igneous rocks deposited in sub horizontal strata. These terrains are configured as residual plateaus above the Southern Brasilia Belt Precambrian metasedimentary lithologies, sustaining a typical appalachian relief, with folded and faulted structures. The evolution of this area involves events of great crustal activity, as the Alto Paranaíba Uplift, and more climatically and tectonically stable moments, when were developed the regional planation surfaces. Although there are available information on the evolution of both morphostructural domains, studies involving areas of transition of them are relatively sparse and lack systematization on the taxonomical level to permit the results’ integration in order to sums up evidences to the evolutive frame of the region. In this work the geological frame is investigated and a geomorphological compartmentation is conducted as subsidies for the elaboration of a relative chronology among the recognized events based on the identification of the geomorphological forms and processes. It is also proposed a relief taxonomy which can be used in further studies in this and other transitional areas. The evidences found in the study area are considered aside the available informations in order to elaborate an evolutive geomorphological frame to the Serra da Canastra’s occidental border.
Evolução geomorfológica da borda ocidental da Serra da Canastra: proposição de taxonomia de relevo para estudos de áreas de transição
Keywords: Geologic and Structural Mapping; Geomorphological Compartmentation; Geomorphological Mapping; Planation Surfaces; Relief Evolution